Theorizing the Decision‐Making Process for Divorce or Reconciliation. Issue 1 (March 2017) - Allen, Sarah; Hawkins, Alan J.
Abstract: Divorce is commonplace in the United States, with an abundant scholarship on the phenomenon. Most research has focused on predictors of divorce, associations between divorce and family member well‐being, and interventions and policies for divorcing couples and children. Although this scholarship tells us much about why couples get divorced and the impact divorce has, it has little to say about how individuals think about and couples talk about and make meaning of their decision‐making process regarding divorce or reconciliation. The purpose of this article is to examine and critique existing theoretical frameworks used to understand decision‐making processes both generally in the field and specifically in the context of divorce ideation. Our goal is to propose future research and theory directions that are better suited to capturing the complexity of decision‐making processes within the liminal space of the lives of individuals who are married but facing the proximate possibility of divorce.